The influence of emotional intelligence and peer social support on subjective well-being in early adolescents at SMP Istiqomah Sambas Boarding School Purbalingga - Sri Muspitasari,; Nia Anggri Noveni,; Suwarti,; Gisella Arnis Grafiyana, (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Adolescence is a period of development marked by upheaval and conflict, which can explain the problems experienced by students at Islamic boarding schools. This is related to students' comfort while living in Islamic boarding schools, which can reduce the level of subjective well-being of teenagers. This research examined the influence of emotional intelligence and peer social support on subjective well-being in early adolescents at SMP Istiqomah Samabas Boarding school Purbalingga. This research uses a quantitative approach with multiple linear regression analysis methods. This research used a saturated sampling technique in which the entire population was sampled, a total of 118 students, with 60 male students and 58 female students. The measuring instruments used are the subjective well-being scale (SwLS and SPANE), the emotional intelligence scale (EII), and the peer social support scale (SSSS). This research shows a significant influence between emotional intelligence and peer social support on subjective well-being, with a value of F=18.158, P=0.000, and R Square of 0.240, meaning that emotional intelligence and peer social support contribute 24% to subjective well-being. It is essential to carry out positive activities to develop emotional intelligence and team activities to foster a sense of friendship to increase high subjective well-being.